MAKNA DAKWAH DALAM LIRIK LAGU ANIMASI NUSSA & RARA: ANALISIS PADA SONG COMPILATIONS VOL 1, 4 & 5 - Ahmad Adnan; Riyadh Nur Hidayatullah (El-Hikmah: Jurnal Ilmu Dakwah dan Komunikasi, 2022)
This study aims to analyze the meaning of da'wah in the song compilation of Nussa and Rara Volumes 1, 4, and 5. This type of research is a qualitative research with qualitative content analysis through interpretation and not counting statistical numbers. The research design used by the author is descriptive analytic research. The research finding is that there are messages of aqidah, sharia and morals in 4 song titles on the Nussa Offical Youtube Channel. The message of faith is to believe in the existence of Allah SWT and His attributes. Believe in angels and supernatural things. The message of Sharia is an invitation to establish sunnah worship on Fridays, such as taking a bath before performing the Friday prayer. In addition, it is an invitation to maintain the purity of intentions because of Allah SWT. The moral message is to maintain etiquette when eating. Keeping the tongue from things that can harm or hurt the feelings of others and glorify parents and fellow Muslims